The Correlation Between Housing Density and House Ventilation Area and the Incidence of Acute Respiratory Tract Infections in Toddlers in Tuminting Sub-District, Manado City - Winiarti M. Andolo; Woodford B S. Joseph; Oksfriani Jufri Sumampouw (CV. Science Tech Group, 2026)
Background: Acute Respiratory Infections (ARI) remain the primary cause of morbidity among children under five in Indonesia, with the domestic physical environment being a significant determinant. Surveillance data from the Tuminting Health Center (2025) indicates an exceptionally high prevalence of ARI (79.0%) in toddlers within Tuminting District, Manado City. Objective: This study aimed to analyze the association between residential occupancy density and house ventilation area with the incidence of ARI in toddlers in this high-prevalence region. Methods: A cross-sectional study was conducted from July to November 2025. A purposive sample of 62 toddlers was enrolled. Primary data were collected via questionnaires, direct observation, and physical measurements of dwellings using a roller meter. Univariate analysis described variable characteristics, and the Fisher's Exact test was employed for bivariate analysis with a significance level of p < 0.05. Results: The majority of households had non-compliant occupancy density (83.9%), while most had adequate ventilation area (91.9%). The ARI prevalence was 79.0%. Bivariate analysis revealed a statistically significant association between high occupancy density and ARI incidence (p-value = 0.004). In contrast, no significant relationship was found between ventilation area and ARI (p-value = 0.280). Conclusion: Occupancy density is the dominant environmental risk factor contributing to the high incidence of ARI in toddlers in Tuminting District. These findings underscore that public health interventions must extend beyond improving physical housing quality (e.g., ventilation) to actively address overcrowding through healthy housing policies and targeted community education.